2006
DOI: 10.1073/pnas.0510695103
|View full text |Cite|
|
Sign up to set email alerts
|

Roles of the anaphase-promoting complex/cyclosome and of its activator Cdc20 in functional substrate binding

Abstract: The anaphase-promoting complex/cyclosome (APC/C) is a multisubunit ubiquitin-protein ligase that targets for degradation cell-cycle regulatory proteins during exit from mitosis and in the G 1 phase of the cell cycle. The activity of APC/C in mitosis and in G 1 requires interaction with the activator proteins Cdc20 and Cdh1, respectively. Substrates of APC/C–Cdc20 contain a recognition motif called the “destruction box” (D-box). The mode of the action of APC/C act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 31 publications
5
52
0
Order By: Relevance
“…Our experiments demonstrate that deletion of either the N-terminus or the C-terminus stabilizes Six1 to degradation by APC Cdh1 . A double recognition motif such as this has been found in other APC Cdh1 substrates (Castro et al, 2005) and may be due to the fact that the core APC, as well as the activators Cdh1 and Cdc20, participate in substrate-binding interactions (Yamano et al, 2004;Passmore and Barford, 2005;Eytan et al, 2006). It is thus possible that the N-terminus of Six1 contains a novel motif important for Cdh1 binding, whereas the C-terminus contains an additional element that binds to the core APC.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our experiments demonstrate that deletion of either the N-terminus or the C-terminus stabilizes Six1 to degradation by APC Cdh1 . A double recognition motif such as this has been found in other APC Cdh1 substrates (Castro et al, 2005) and may be due to the fact that the core APC, as well as the activators Cdh1 and Cdc20, participate in substrate-binding interactions (Yamano et al, 2004;Passmore and Barford, 2005;Eytan et al, 2006). It is thus possible that the N-terminus of Six1 contains a novel motif important for Cdh1 binding, whereas the C-terminus contains an additional element that binds to the core APC.…”
Section: Discussionmentioning
confidence: 90%
“…Recent evidence indicates that Cdh1 and Cdc20 interact specifically with the D-box and KEN box destruction motifs of their substrates (Burton et al, 2005;Kraft et al, 2005). Thus, it is has been suggested that substrates lacking canonical D-boxes may contain a three-dimensional interaction surface similar to a D-box but with differing primary amino acid sequence (Eytan et al, 2006). Our experiments suggest that the Nterminus of Six1 contains a novel motif mediating interaction with Cdh1 and directing APC Cdh1 -mediated degradation of Six1, as deletion of the N-terminus stabilizes Six1 to degradation mediated by APC Cdh1 and GST pull-down experiments indicate that the N-terminus alone is sufficient for binding to Cdh1.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of multiple targeting signals on Cyclin A is consistent with a model wherein both core APC/C subunits and coactivators contribute to substrate recognition. 16,17 Further work is needed to decipher how the cyclin box functions as a destruction signal.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 As a compromise between these two opposing hypotheses, new studies indicate that both the APC/C and its coactivators contribute to substrate recognition. 16,17 Drosophila has three mitotic cyclins: Cyclin A (CycA), Cyclin B (CycB) and Cyclin B3 (CycB3). Their sequential degradation facilitates mitotic exit.…”
Section: Introductionmentioning
confidence: 99%
“…Cdh1 or Cdc20 Can Stimulate Nlp Degradation-It has been demonstrated that Cdc20 (Fizzy in Drosophila) and a related protein Cdh1 (Fizzy-related in Drosophila) activate APC through giving temporal control and substrate specificity to the APC/c E3 ligase (25,26). Each of these two activators physically associates with APC in a cell cycle-dependent manner and stimulates substrate degradation.…”
Section: Nlp Protein Stability Is Regulated By Anaphase-promotingmentioning
confidence: 99%